2021
DOI: 10.1101/2021.01.21.427698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into animal septins using recombinant human septin octamers with distinct SEPT9 isoforms

Abstract: Septin GTP-binding proteins contribute essential biological functions that range from the establishment of cell polarity to animal tissue morphogenesis. Human septins in cells form hetero-octameric septin complexes containing the ubiquitously expressed SEPT9. Despite the established role of SEPT9 in mammalian development and human pathophysiology, biochemical and biophysical studies have relied on monomeric SEPT9 thus not recapitulating its native assembly into hetero-octameric complexes. We established a prot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 118 publications
0
34
0
Order By: Relevance
“…The discrepancy is most likely linked to the fact that in these in vitro experiments, Sept9 was used outside of its natural octameric context, often at high concentrations (up to 10-30 µM in pelleting assays) and using paclitaxel or GMPCPP stabilized microtubules in very low salt buffers, which likely favored electrostatic interactions. Using recombinant octamers harboring Sept9_i1 and Sept9_i3 12 , we observed that only those harboring Sept9_i1 associated with dynamics microtubules at low nanomolar concentrations, in vitro. Our in vitro reconstitution experiments results are the first one to recapitulate the specific binding of Sept9_i1 octamers to microtubules observed in cells here and by others 40,52 .…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…The discrepancy is most likely linked to the fact that in these in vitro experiments, Sept9 was used outside of its natural octameric context, often at high concentrations (up to 10-30 µM in pelleting assays) and using paclitaxel or GMPCPP stabilized microtubules in very low salt buffers, which likely favored electrostatic interactions. Using recombinant octamers harboring Sept9_i1 and Sept9_i3 12 , we observed that only those harboring Sept9_i1 associated with dynamics microtubules at low nanomolar concentrations, in vitro. Our in vitro reconstitution experiments results are the first one to recapitulate the specific binding of Sept9_i1 octamers to microtubules observed in cells here and by others 40,52 .…”
Section: Discussionmentioning
confidence: 92%
“…Recombinant septin octamers harboring Sept9_i1 interact directly and specifically with microtubules and slow down their depolymerization. In order to assess if recombinant octamers harboring (Oct_9i1) are able to bind directly to microtubules, we purified recombinant septin octamers (Sept2-Sept6-Sept7-Sept9_i1-Sept9_i1-Sept7-Sept6-Sept2 and Sept2-Sept6-Sept7-Sept9_i3-Sept9_i3-Sept7-Sept6-Sept2) 12 (Supplementary Fig. 1b) and reconstituted dynamic microtubules made from purified tubulin /-heterodimers in the presence of each type of octamer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations